Perlindungan Hukum Pengguna Sepeda Listrik Di Kota Semarang - Putri Haliza Yuniar; Endah Pujiastuti; Zaenal Arifin; Sonny Hendraprasanto (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze legal protection for electric bicycle users in Semarang City and to identify regulatory implementation challenges as well as strategies for strengthening such protection. The increasing use of electric bicycles as an environmentally friendly mode of transportation has raised concerns regarding safety and legal certainty, particularly because their regulation remains dispersed across multiple legal regimes that have not been comprehensively integrated. The urgency of this research arises from the growing number of electric bicycle accidents and the lack of normative coherence between traffic law and consumer protection law, which creates uncertainty regarding legal responsibility. This research employs a socio-legal approach with a descriptive-analytical specification through interviews, literature review, and qualitative analysis to examine the alignment between legal norms and their implementation in practice. The novelty of this study lies in developing an integrated legal protection analysis combining traffic law and consumer protection law by positioning electric bicycle users as dual legal subjects, while also testing its effectiveness in the local context of Semarang City. The findings indicate that legal protection is normatively available but remains ineffective due to regulatory disharmony, weak institutional supervision, low public compliance, and the absence of comprehensive statutory regulation. Therefore, regulatory harmonization, strengthened supervision, safety infrastructure development, and systematic legal reform are necessary to ensure effective legal protection.  Penelitian ini bertujuan menganalisis perlindungan hukum bagi pengguna sepeda listrik di Kota Semarang serta mengidentifikasi kendala implementasi regulasi dan strategi penguatannya. Peningkatan penggunaan sepeda listrik sebagai moda transportasi ramah lingkungan menimbulkan persoalan keselamatan dan kepastian perlindungan hukum, terutama karena pengaturannya masih tersebar dalam berbagai rezim hukum yang belum terintegrasi secara komprehensif. Urgensi penelitian ini didasarkan pada meningkatnya angka kecelakaan sepeda listrik serta adanya ketidaksinkronan norma antara hukum lalu lintas dan hukum perlindungan konsumen yang berimplikasi pada ketidakpastian tanggung jawab hukum. Penelitian menggunakan pendekatan yuridis sosiologis dengan spesifikasi deskriptif analitis melalui wawancara, studi kepustakaan, dan analisis kualitatif untuk menilai kesesuaian antara norma hukum dan implementasinya dalam praktik. Kebaruan penelitian terletak pada pengembangan analisis perlindungan hukum berbasis integrasi rezim hukum lalu lintas dan hukum perlindungan konsumen dengan menempatkan pengguna sepeda listrik sebagai subjek hukum ganda sekaligus menguji efektivitasnya pada konteks lokal Kota Semarang. Hasil penelitian menunjukkan bahwa perlindungan hukum secara normatif telah tersedia, namun efektivitasnya masih terbatas akibat disharmonisasi regulasi, lemahnya pengawasan kelembagaan, rendahnya kepatuhan masyarakat, serta belum adanya pengaturan komprehensif pada tingkat undang-undang. Oleh karena itu, diperlukan harmonisasi regulasi, penguatan pengawasan, penyediaan infrastruktur keselamatan, dan pembaruan hukum yang lebih sistematis guna menjamin perlindungan hukum yang efektif.